Retrospective Study: Management of Atopic Dermatitis - Nanny Herwanto; Marsudi Hutomo (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Atopic dermatitis (AD) is a chronic skin inflammatory disease, characterized with mild to severe itching, relapses, and mostly appears in infants and children. Although there has been current advances in the management of AD but satisfactory treatment has not been obtained. Purpose: To evaluate the treatment of patients with AD, hence better management can be provided. Methods: Retrospective study of newly diagnosed AD patients in Allergy Immunology Division of Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya during 2012-2014. Result: Antihistamine is the most widely prescribed medication, as many as 234 (36.3%) of all patients visits and cetirizine was the most given antihistamine in 142 (58%) of the patients. Emollients still used minimally, such as urea 10% cream in 71 (11%) patients, ambiphilic cream (biocream®) in 52 (8.1%) patients, and vaseline album in 11 (1.7%) patients. Conclusion: Emollients therapy is important in the management of AD and hence its usage should be adequate.Key words: atopic dermatitis, management, retrospective.